Synthesis and Characterization of Some new 2,4-Thiazolidinedione Derivatives - Zina. S. Hassan (Journal of Global Pharma Technology, 2019)
The synthesized thiazolidinedione compounds were prepared from the condensation reaction between chloroacetic acid with thiourea in the presence of water. The yield of product was found to be in the range of 75-95%. The second-pot synthesized 2, 4-thiazolidinedione derivatives were prepared from the condensation reaction between thiazolidine ring with series of aldehydes aromatic (4-(Dimethylamino) benzaldehyde, 2, 3-Dimethoxybenzaldehyde, Terephathaldehyde, 2-Thiophenecarboxaldehyde, Isatin, Furfural) and confirmed by spectral data: FTIR and 1H-NMR Spectra.Keywords: 2, 4- thiazolidinedione; Characterization; Thiourea.